In-situ constructing a rigid and stable dual-layer CEI film improving high-voltage 4.6 V LiCoO2 performances. (1st June 2022) - Qin, Yinping; Xu, Kaiyun; Wang, Qian; Ge, Menghan; Cheng, Tao; Liu, Meng; Cheng, Hongyu; Hu, Yibo; Shen, Cai; Wang, Deyu; Liu, Yang; Guo, Bingkun
Abstract: As the most important cathode used in digital devices, LiCoO2 can extract more specific capacity by lifting the operational voltage. But the cyclic performance suffers from rapid decay due to the unstable electrode/electrolyte interphase (CEI) at high voltage. In this work, a novel in-situ dual-layer CEI film with high electrochemical stability and mechanical strength is constructed by sequential oxidation potentials of multiply additives. The inner layer of fluorinated-alkyl amide compounds displays a good oxidative stability to ~4.75 V vs. Li + /Li, and the outer layer of polymerized diphenylamine (DPA) shows an ultrahigh Young's modulus ~ 25.4 GPa. This dual-layer CEI film not only prevents the decomposition of electrolyte and dissolution of Co element, but also mitigates the particles cracking. With the protection of this dual-layer CEI film, the capacity retention of Li/LiCoO2 cells has been improved from ~ 59% to 75% at 4.6 V vs. Li + /Li in 200 cycles. This work provides a new design of constructing stable CEI film for high-energy-density lithium ion batteries (LIBs). Graphical Abstract: A dual-layer CEI film with excellent oxidation stability and ultrahigh mechanical strength is in-situ constructed via a simple approach of multiply additives in electrolyte. ga1 Highlights: A novel dual-layer CEI film with high oxidation stability and mechanical strength. In-situ constructing a dual-layer CEI film via the sequential oxidation of multiply additives. Improving the capacity retention of 4.6 V LiCoO2 electrodes from ~ 59% to 75% in 200 cycles.